DOOR SECURITY SYSTEM FOR HOME MONITORING BASED ON IOT - Tiwari, Anurag; Waoo, Akhilesh A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The smart door lock system Using IoT is an innovative solution that combines the power of Internet of Things (IoT) technology with traditional door locking mechanisms to enhance security, convenience, and control. This system employs smart devices, sensors, and a cloud-based platform to create an intelligent and responsive door access management system. The core components of the smart door lock system include a smart door lock device, IoT-enabled sensors, and a centralized cloud-based platform. The smart door lock is equipped with electronic locking mechanisms and wireless communication capabilities, allowing it to be controlled remotely. The IoT sensors integrated into the door and surrounding environment, provide real-time data on various parameters such as door status, temperature, and motion. The system utilizes a secure and scalable cloud-based platform to manage and monitor access control. Users can interact with the smart door lock system through a dedicated mobile application, web interface, or voice commands. The cloud platform enables seamless integration with other smart home devices and provides a centralized hub for data storage and analysis. The smart door lock system using IoT addresses the growing need for advanced security solutions while offering users unprecedented control over their door access. Making it a valuable addition to modern households and commercial spaces.